The Role of AI-Driven Generative Design in Enhancing Visual Communication: A Computational Creativity Approach - McLeena, McLeena; Laura, Jenn (International Journal of Graphic Design, 2026)
The integration of artificial intelligence (AI) in graphic design has led to the emergence of generative design, a technique that automates and optimizes visual composition through computational creativity. This study explores the impact of AI-driven generative design on visual communication, focusing on its effectiveness in enhancing creativity, efficiency, and user engagement. The research employs a mixed-method approach, combining quantitative analysis of AI-generated visual outputs with qualitative insights from professional designers. Experimental evaluations were conducted using AI-based design tools to generate branding materials, advertisements, and digital media assets, followed by comparative assessments with human-created designs. The findings reveal that AI-driven generative design significantly improves workflow efficiency by reducing design iteration time by 40% while maintaining high aesthetic appeal. Moreover, AI-enhanced visual communication demonstrates increased adaptability to diverse audience preferences, as evidenced by a 25% improvement in user engagement metrics. Despite these advantages, ethical concerns regarding originality and authorship remain key challenges in AI-assisted creative processes. This study contributes to the ongoing discourse on AI integration in the creative industry by providing empirical evidence on the role of computational creativity in shaping the future of graphic design. The results suggest that AI-driven generative design can serve as a collaborative tool rather than a replacement for human designers, fostering innovation and efficiency in visual communication.